The IKK/NF-κB signaling pathway requires Morgana to drive breast cancer metastasis. Issue 1 (December 2017) - Fusella, Federica; Seclì, Laura; Busso, Elena; Krepelova, Anna; Moiso, Enrico; Rocca, Stefania; Conti, Laura; Annaratone, Laura; Rubinetto, Cristina; Mello-Grand, Maurizia; Singh, Vijay; Chiorino, Giovanna; et al.
Abstract NF-κB is a transcription factor involved in the regulation of multiple physiological and pathological cellular processes, including inflammation, cell survival, proliferation, and cancer cell metastasis. NF-κB is frequently hyperactivated in several cancers, including triple-negative breast cancer. Here we show that NF-κB activation in breast cancer cells depends on the presence of the CHORDC1 gene product Morgana, a previously unknown component of the IKK complex and essential for IκBα substrate recognition. Morgana silencing blocks metastasis formation in breast cancer mouse models and this phenotype is reverted by IκBα downregulation. High Morgana expression levels in cancer cells decrease recruitment of natural killer cells in the first phases of tumor growth and induce the expression of cytokines able to attract neutrophils in the primary tumor, as well as in the pre-metastatic lungs, fueling cancer metastasis. In accordance, high Morgana levels positively correlate with NF-κB target gene expression and poor prognosis in human patients. NF-κB regulates inflammation, cell survival, proliferation, and metastasis and is often hyperactivated in triple-negative breast cancer. Here the authors show that Morgana, a protein highly expressed in triple-negative breast cancers, drives NF-kB activation to promote metastasis and neutrophil recruitment.